Political Marketing Mix Mahasiswa Dalam Pilgub Jabar 2018 - Gia Septian, Mochamad Ilyas; Utama, R Dian H.; Purnama, Ridwan (Journal of Business Management Education (JBME), 2019)
ABSTRACT:Â This study aims to describe the political marketing mix and the decision to elect the Governor and deputy governor of West Java in 2018 to students of the Indonesian Education University. This study uses a descriptive approach with the explanatory survey method. The unit of analysis is the 2013-2017 UPI undergraduate students with 106 people. Data collection is done using a questionnaire. The analysis technique used is a descriptive technique using frequency distribution. The findings in this study show that the picture of the political marketing mix is in a fairly good category, and the picture of the decision to choose is in a fairly good category, and the political marketing mix has a significant influence on the decision to choose with a quite high influence of 62%. The difference in this study lies in the object of research, the time of the study, the measuring instrument, the literature used, the theory used and the results of the study.Â